Impact of derivative usage on firm’s risk and value: a comparative analysis of Pakistan and Malaysia - Alam, Atia; Afza, Talat (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
This study empirically examines the effect of derivative usage on firm’s risk and value by employing sample data of Pakistani and Malaysian listed companies for the period of 2004- -2010. Supporting the risk management use of derivative instruments, the study finds that the usage of derivative instruments significantly minimizes firm’s risk, with respect to operating cash flow variability in both Pakistan and Malaysia, although the extent of risk reduction is higher in Malaysian firms. While considering variability in earning per share as a firm’s risk, the findings imply that Pakistani firm’s earning per share variability is irrelevant for firm’s derivative usage, whereas Malaysian firms are able to minimize such volatility by using derivative instruments. The results show the insignificant effect regarding the relationship of derivative usage with firm’s value of Malaysian corporations, indicating that as Malaysia has developed capital market and firms are more geographically diversified in comparison to Pakistan, thus their value relevance of derivative usage are limited. While in the case of Pakistan, the use of derivative instruments significantly enhances firm’s value
Argumenta Oeconomica, 2017, Nr 1 (38), s. 221-242
Keywords: foreign currency derivatives; interest rate derivatives; firm value; firm risk; Pakistan